2009
DOI: 10.1530/rep-08-0539
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulatory control for uterine stromal cell decidualization in implantation

Abstract: Uterine stromal cell decidualization is integral to successful embryo implantation, which is a gateway to pregnancy establishment. This process is characterized by stromal cell proliferation and differentiation into decidual cells with polyploidy. The molecular mechanisms that are involved in these events remain poorly understood. The current concept is that locally induced factors with the onset of implantation influence uterine stromal cell proliferation and/or differentiation through modulation of core cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
153
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(163 citation statements)
references
References 82 publications
8
153
0
2
Order By: Relevance
“…These results indicate that Tdo2 may be involved in mouse decidualization. Decidualization is a process which is characterized by uterine stromal cells proliferating and differentiating into decidual cells with polyploidy (Das 2009). This study showed that Tdo2 could regulate the proliferation of uterine stromal cells and decidual cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that Tdo2 may be involved in mouse decidualization. Decidualization is a process which is characterized by uterine stromal cells proliferating and differentiating into decidual cells with polyploidy (Das 2009). This study showed that Tdo2 could regulate the proliferation of uterine stromal cells and decidual cells.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of implantation in mice is characterized by a localized increase in uterine vascular permeability at the site of the blastocyst attachment, which occurs in the midnight of day 4 of pregnancy and can be visible by intravenous injection of Chicago blue dye (blue reaction) [20]. Coincidently, stromal cells immediately surrounding the implanting blastocyst undergo extensive proliferation and subsequently differentiate into specialized cells that are polyploidy, and this process is known as decidualization [26]. This extensive cell proliferation and polyploidy event occurs in a well-organized manner.…”
Section: Uterine Physiological Role In Normal Reproductive Eventsmentioning
confidence: 99%
“…Underneath the epithelium, there is a loose connective tissue layer with stromal cells, glands, and blood vessels. Many uterine functions are under the regulation of ovarian steroid hormones, estrogens and progesterone (P 4 ; Dey et al 2004, Das 2009), and uterine cell types respond to hormones in a differential manner. Ovarian estrogen targets uterine epithelial cells, inducing proliferation and differentiation of these cells, whereas the proliferation of uterine stromal cells is under P 4 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these hormones prepare the uterus for embryo implantation, a process that begins around midnight of day 4 of pregnancy. Thus, P 4 and estrogen are crucial regulators of cell cycle and cellular differentiation in the uterus (Das 2009). …”
Section: Introductionmentioning
confidence: 99%